2009
DOI: 10.1126/science.1181369
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Mapping of Long-Range Interactions Reveals Folding Principles of the Human Genome

Abstract: We describe Hi-C, a method that probes the three-dimensional architecture of whole genomes by coupling proximity-based ligation with massively parallel sequencing. We constructed spatial proximity maps of the human genome with Hi-C at a resolution of 1Mb. These maps confirm the presence of chromosome territories and the spatial proximity of small, gene rich chromosomes. We identified an additional level of genome organization that is characterized by the spatial segregation of open and closed chromatin to form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

463
9,601
9
45

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7,837 publications
(10,118 citation statements)
references
References 35 publications
463
9,601
9
45
Order By: Relevance
“…[10], see Methods for details) and mutual ranks of gene co-expression rates (provided by COXPRESdb[11]). We controlled the effect of transcription factors on co-expression using transcription control similarity (TCS, see Methods for details) [12], and used 6,084 genes with both TF annotation (from ITFP[13]) and co-expression information for analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10], see Methods for details) and mutual ranks of gene co-expression rates (provided by COXPRESdb[11]). We controlled the effect of transcription factors on co-expression using transcription control similarity (TCS, see Methods for details) [12], and used 6,084 genes with both TF annotation (from ITFP[13]) and co-expression information for analyses.…”
Section: Resultsmentioning
confidence: 99%
“…One of the well-known models for such structure is open and closed chromatin [10,12]. Under an assumption that sequence-neighboring genes have a similar chromatin structure, N. Batada et al found that these genes have higher co-expression rates than separate ones [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The improper coordination of chromosome condensation and segregation during the cell cycle can lead to important structural abnormalities and result in cell death or diseases such as cancer (Valton & Dekker, 2016). In recent years, major advances in imaging and chromosome conformation capture approaches (Dekker et al , 2002; Lieberman‐Aiden et al , 2009; 3C, Hi‐C) have complemented earlier work by describing at an unprecedented resolution the multiple hierarchical layers of genome organization. A variety of remarkable 3D chromosomal structures have been described in a number of species, including in unicellular organisms such as bacteria and yeasts.…”
Section: Introductionmentioning
confidence: 99%
“…To explore new chromosomal structural features over the cell cycle progression, we analyzed the internal folding and overall organization of S. cerevisiae genome over 15 synchronized time points and the role of cohesin and condensin using Hi‐C (Dekker et al , 2002; Lieberman‐Aiden et al , 2009). This analysis provides a broad overview and in‐depth insight on SMC‐dependent structural transitions resulting in chromosome individualization and segregation, including a potential role for a condensin‐dependent loop in contributing to the segregation of the rDNA cluster.…”
Section: Introductionmentioning
confidence: 99%